Manajemen Pemberdayaan Masyarakat dalam Mempertahankan Eksistensi Sekolah di SD IT Rabbani - Sulaeman Sulaeman; Hastina Hastina (Adaara: Jurnal Manajemen Pendidikan Islam, 2021)
This study describes the management of community empowerment in maintaining the existence of schools at SD IT Rabbani. The author applied qualitative research. The data was analyzed in the process of data reduction method, presentation of data and drawing conclusions. Furthermore, deductive thinking is used, namely taking some general facts which are then analyzed to apply specific things. SD IT Rabbani adheres to a community empowerment management system in maintaining school existence, where the school provides sufficient space for parents to take part in the planning process, policy determination to decision making. Therefore, with the management of Community Empowerment Management, it turns out to be able to have a very significant impact, especially in achieving the school's vision, objectives and goals so as to be able to maintain the existence of SD IT Rabbani. The Community Empowerment Management has been able to make SD IT Rabbani one of the leading schools that are in great demand by the community who search for elementary school.